Distribution Pattern of N6-Methyladenine DNA Modification in the Seashore Paspalum (Paspalum vaginatum) Genome - Hao, Jiang-Shan; Xing, Jian-Feng; Hu, Xu; Wang, Zhi-Yong; Tang, Min-Qiang; Liao, Li (Frontiers in Plant Science, 2022)
N6-methyladenine (6mA) DNA modification has been detected in several eukaryotic organisms, in some of them it plays important roles in regulation process of stress-resistance response. However, the genome-wide distribution patterns and potential functions of 6mA DNA modification in halophyte Seashore paspalum (Paspalum vaginatum) remain largely unknown. Here, we examined the 6mA landscape in the P. vaginatum genome by adopting single molecule real-time sequencing technology and found that 6mA modification sites were broadly distributed across the P. vaginatum genome. We demonstrated distinct 6mA methylation level and 6mA distribution pattern in different types of transcription genes, which hinted at different epigenetic rule. Furthermore, the moderate 6mA density genes in P. vaginatum functionally correlated with stress resistance, which also maintained higher transcriptional level. On the other hand, specific 6mA distribution pattern in the gene body and near TSS was observed in genes groups with higher RNA expression, which maybe implied that some kind of regularity between 6mA site distribution and the protein coding genes transcription was possible. Our study provides new insights into the association with 6mA methylation and gene expression, which may also contribute to key agronomic traits in P. vaginatum.